Protein-induced delubrication: How plant-based and dairy proteins affect mouthfeel. (January 2023) - Vlădescu, Sorin-Cristian; Agurto, Maria Gonzalez; Myant, Connor; Boehm, Michael W.; Baier, Stefan K.; Yakubov, Gleb E.; Carpenter, Guy; Reddyhoff, Tom
Abstract: Understanding how certain proteins cause astringency is necessary in order to improve the mouthfeel and popularity of plant-based foods. To this end, we studied protein interactions during oral processes using a PDMS-PDMS interface lubricated by ex-vivo human saliva. Friction measurements and in-contact imaging were implemented, while food consumption was simulated by introducing model plant and animal-based proteins. All but one of the protein samples caused an increase in measured friction and this correlated with astringency ratings from a human taste panel. This is attributed to delubrication as the salivary pellicle is removed, since food proteins interact with salivary proteins thus disrupting their adhesion. This interaction is shown to occur both on the surface and in the bulk of the fluid. However, the debonding of the pellicle requires frictional shear stress (i.e., rubbing) . Food proteins in isolation are themselves shown to be surface-active and form boundary films, which can adhere following removal of the pellicle. The mechanical action of protein particles in the delubrication process was isolated by filtering and shown to account for a moderate (<33%) increase in friction magnitude accompanied by a significant (>90%) increase in frictional noise. The flow and deformation of these particles was also visualised thus demonstrating how the microscale breakdown of food can be studied. Graphical abstract: Image 1 Highlights: Tribological tests and fluorescence imaging were used to study the breakdown of the salivary pellicle by food proteins. During salivary pellicle formation, salivary proteins agglomerations are trapped at the inlet and act to feed the contact. Plant proteins can cause astringency by interacting with saliva proteins both on the surface and in the bulk of the fluid. Friction increase resulting from introduction of food protein correlated with astringency ratings from a human taste panel. Shear stress is required to remove the weakly bound saliva proteins to cause delubrication.